Croton lindquistii (Euphorbiaceae): a new arborescent species from western Mexico - Steinmann, Victor W. (Phytotaxa, 2014)
Croton lindquistii, a new species in Croton subg. Geiseleria sect. Eluteria subsect. Eluteria, is described and illustrated. It occurs in the tropical deciduous forests of western Mexico from Sonora to Oaxaca. The species is economically important, and during the past four decades, plants have been extensively harvested for their straight, hard, and durable trunks that are used as fence posts and stakes in agricultural fields. Although the exact affinities of C. lindquistii are unknown, it is similar to both C. niveus and C. pseudoniveus. It differs from the former by having ovate to cordiform leaves, fruiting pedicels less than 3 mm long, and spiciform thyrses that are very compact with the axis obscured by the buds. It differs from the latter by having 15–16 stamens per flower and stellate-pubescent ovaries and fruits. The name Croton fantzianus has been misapplied to Croton lindquistii. A key is provided that distinguishes the new species from the five other members of Croton sect. Eluteria subsect. Eluteria that have ovaries and fruits with stellate pubescence.